2011
DOI: 10.1088/0067-0049/195/2/13
|View full text |Cite
|
Sign up to set email alerts
|

Improved and Quality-Assessed Emission and Absorption Line Measurements in Sloan Digital Sky Survey Galaxies

Abstract: We present a new database of absorption and emission-line measurements based on the entire spectral atlas from the Sloan Digital Sky Survey (SDSS) 7 th data release of galaxies within a redshift of 0.2. Our work makes use of the publicly available penalized pixel-fitting (pPXF) and gas and absorption line fitting (gandalf) IDL codes, aiming to improve the existing measurements for stellar kinematics, the strength of various absorption-line features, and the flux and width of the emissions from different specie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
211
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(223 citation statements)
references
References 56 publications
9
211
0
Order By: Relevance
“…Indeed the differences between pairs of measurements closely match those predicted by their uncertainties. The good agreement of the flux measurements obtained by Oh et al (2011) using a different approach for the removal of the stellar emission also supports the robustness of those provided by MPA-JHU database.…”
Section: Emission Lines and Stellar Continuumsupporting
confidence: 73%
“…Indeed the differences between pairs of measurements closely match those predicted by their uncertainties. The good agreement of the flux measurements obtained by Oh et al (2011) using a different approach for the removal of the stellar emission also supports the robustness of those provided by MPA-JHU database.…”
Section: Emission Lines and Stellar Continuumsupporting
confidence: 73%
“…The velocity widths (deconvolved for the instrumental broadening) of [O ii]λλ3727,3729 doublet (i.e.,σ [O II] ) is found in the range of ∼ 17 ± 16 km s −1 to 194 ± 72 km s −1 in SDSS-DR7 and 6 ± 11 km s −1 to 198 ± 91 km s −1 in the SDSS-DR12 spectra with an average σ [O II] of ∼ 75 km s −1 . This is similar to a typical velocity dispersion found in the SDSS galaxies (Oh et al 2011). The KS − test does not indicate any differences between the σ [O II] in SDSS-DR7 and DR12 with p null = 0.23.…”
Section: Velocity Width Of Emission and Mass Ofsupporting
confidence: 84%
“…Groves et al (2012) have indeed shown that, for a fixed age of the underlying stellar population, different population synthesis models give differences in the Hβ and Hα Balmer absorption lines up to ∼2−3 Å. There are also indications that the use of different fitting procedures can lead to different measurements of line emission, in particular whenever the emission is weak (Oh et al 2011). For these reasons we prefer to adopt a simpler approach by directly measuring the underlying absorption in the Hβ line from the spectra, and use a constant correction for the Hα line.…”
Section: Contribution Of the Underlying Balmer Absorptionmentioning
confidence: 99%
“…The set of spectroscopic data in our hand is thus quite non homogeneous in terms of S/N. Since the accuracy of the fit depends on the S/N (Oh et al 2011), these spectra can be hardly used without other photometric data to constrain the star formation history of the target galaxies and measure the underlying Balmer absorption using population synthesis models.…”
Section: Contribution Of the Underlying Balmer Absorptionmentioning
confidence: 99%